Promoting Sustainability Through Green Chemistry, Part 2 - Paryjczak, Tadeusz (Problemy Ekorozwoju, 2008)
Green Chemistry is an important tool in the achievement of sustainability. Its implementation, along with the design of chemical products and processes that reduce or eliminate the use and generation of hazardous substances, is essential if the expanding global populations are to enjoy an increased standard of living without exerting a negative impact on the health of the planet. One of the major goods of sustainability is the maintenance of an optimal balance between increased manufacturing output and a clean and safe environment. Cleaner technologies will allow chemical enterprises to provide society with the good and services on which it depends, albeit in an environmentally responsible manner. Green chemistry can provide solutions for such global challenges as climate change, sustainable agriculture, energy, toxics in the environment and the depletion of natural resources. A collaborative effort by industry, the academic world and government is needed to promote the adoption of the green chemistry technologies necessary to put a sustainable society in place.